Fabrication of aliovalent (aluminum, tin, tantalum) and isovalent (cobalt, manganese) doping engineered zinc oxide-based nanocomposite film for triboelectric nanogenerator applications - Kamaruzaman, Dayana (2025)
Triboelectric nanogenerator (TENG) has been explored as a potential candidate for energy harvesting applications, converting mechanical energy from the surrounding environment to electricity. However, the performance issues of the TENG are primarily attributed to the selection of triboelectric materials used and the adverse effects of high humidity on its functionality, restricting the practical expansion of TENG applications. With the motivation to reduce environmental pollution and the increasing demand for sustainable energy solutions, this research aimed to investigate the generation of electricity by utilizing synthesized zinc oxide nanopowder integrated with polystyrene waste (ZNP/wPS) nanocomposite film as a triboelectric layer for TENG applications. The effects of isovalent and aliovalent dopants (Mn²⁺, Co²⁺, Al³⁺, Sn⁴⁺, and Ta⁵⁺) on the ZNP/wPS nanocomposite film were systematically investigated to optimize the electrical output performance of the TENG. The ZNP and isovalent and aliovalent doped ZNP (Y-ZNPs) were successfully synthesized via the low-temperature solution immersion method whereas the ZNP/wPS and Y-ZNP/wPS nanocomposite films were prepared by a simple dry-casting method. The wPS was sourced from an unused packaging box labelled with the code PS-6. Further, the stearic acid (SA) treatment was employed to enhance the hydrophobicity of both nanocomposite films. Comprehensive characterization of the synthesized materials, including ZNP and Y-ZNPs and their corresponding nanocomposite films (ZNP/wPS and Y-ZNP/wPS), both before and after SA treatment, was conducted using FESEM and TEM for surface morphology analysis, XRD and HRTEM for structural properties, EDS, FTIR and XPS for surface chemical composition analysis and WCA for wettability properties. The TENG were fabricated in a vertical contact-separation configuration using Kapton film as the negative triboelectric layer paired with various positive triboelectric layers including wPS film, ZNP/wPS nanocomposite film, Y-ZNP/wPS nanocomposite film, SA treated ZNP/wPS nanocomposite film and SA treated Y-ZNP/wPS nanocomposite film. The TENG performance was determined using custom-build solenoid tapping system that provided external force onto the fabricated TENG devices. The experimental results demonstrated progressive enhancements in TENG performance. The ZNP/wPS TENG showed a twofold increase in output voltage (8 V) compared to the wPS TENG. Further improvement was achieved with the aluminum doped ZNP/wPS (AZNP/wPS) TENG, which exhibited a twofold voltage increase (16 V) relative to the ZNP/wPS TENG. Subsequently, the SA treated AZNP/wPS TENG yielded the highest open-circuit voltage of 20 V with a power density of 39 μW/cm², comparable to values reported in the literature. These findings highlight the cumulative benefits of incorporating ZNP, aluminum doping, and SA treatment in enhancing TENG performance. SA treatment significantly enhanced the hydrophobicity of the nanocomposite films, with SA treated ZNP/wPS and SA treated AZNP/wPS films exhibiting water contact angles of 135° and 140°, respectively. Both nanocomposite films demonstrate potential as efficient mechanical energy harvesters with high electrical output and excellent surface wettability. Furthermore, the fabricated TENGs demonstrated practical applications in sensing, biomechanical motion detection, and powering portable electronics. This novel approach, incorporating wPS with ZNP in TENG devices, holds significant potential for advancing circular economy principles and supporting sustainable development goals through innovative waste management and energy harvesting solutions.